2017
DOI: 10.1037/mot0000059
|View full text |Cite
|
Sign up to set email alerts
|

A motivational climate intervention and exercise-related outcomes: A longitudinal perspective.

Abstract: While researchers have suggested that the social context in exercise settings is linked to individuals' physical activity motivation and potential exercise-related outcomes, few research designs have examined the nuance of those relationships. Moreover, interventions targeting the social context of exercise settings are sparse, so the potential impact of staff training on members' motivation to exercise are not well known. Drawing from two major motivation theories, achievement goal perspective theory and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
(150 reference statements)
2
5
0
Order By: Relevance
“…The purpose of this study was to examine the relationship between college students’ perceptions of the climate at their CRC to their feelings of thriving, effort, and enjoyment within that setting. Results revealed strong support for the hypothesized relationships among the variables and aligned with previous CRC research (Brown et al, 2015; Brown & Fry, 2015b: Scott et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The purpose of this study was to examine the relationship between college students’ perceptions of the climate at their CRC to their feelings of thriving, effort, and enjoyment within that setting. Results revealed strong support for the hypothesized relationships among the variables and aligned with previous CRC research (Brown et al, 2015; Brown & Fry, 2015b: Scott et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Pre- and post-tests revealed that members’ perceptions of the staff and their own positive behaviors increased significantly after the intervention. Researchers have reported several additional influential outcomes, such as commitment to exercise, positive body image, life satisfaction, perceived competence, higher effort and enjoyment, self-esteem, objective performance, intrinsic forms of motivational regulation, positive affect, adaptive practice and competitive strategies, moral attitudes, and the experience of flow (Brown et al, 2015; Harwood et al, 2015; Hogue et al, 2017).…”
mentioning
confidence: 99%
“…A sample item is "On this team, athletes feel welcome every day", and athletes responded to the items using a 5-point Likerttype scale (1 ¼ strongly disagree and 5 ¼ strongly agree). Previous research has found the CCS to be internally reliable among college-aged participants (a ¼ .96; Brown et al, 2017;a ¼ .92, Newton et al, 2007).…”
Section: Methodsmentioning
confidence: 90%
“…Interventions which give participants both information and the skills to positively change their behaviours (Fishbach & Hofmann, 2015;Sin & Lyubomirsky, 2009) result in increased quality of life (Bonow et al, 2012;Folette et al, 2001). As such, the Mindfulness-based Quality of Life and Well-Being Program (MQW) was made up of both psychoeducation and interactive exercises, and participants were invited to apply the program to their life circumstances so as to consolidate treatment gains (Brown et al, 2017).…”
Section: Program Developmentmentioning
confidence: 99%